The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0040517520972482
|View full text |Cite
|
Sign up to set email alerts
|

Seawater as an alternative to dye cotton fiber with reactive dyes

Abstract: The textile industry is a sector completely dependent on water for its full functioning; on the other hand, water represents a very high cost in the production process. The textile chemical processing area is mainly responsible for the large consumption of water. On the opposite side of this high consumption there is an evident water crisis worldwide. That fact has led to many problems to textile companies, mainly for the preparation, dyeing and printing sectors. This present work focuses on an ecologically fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Since 2000 several papers have demonstrated that organochlorinated compounds, pharmaceuticals, plasticizers, industrial additives, among others, are present in seawater causing its pollution [20] , [76] , [77] , [78] . Also, we can mention that seawater has great potential as a processing medium for dyeing steps in the textile industry, resulting in seawater waste loaded with dyes [79] , [80] . Therefore, many proofs of concept about the sonochemical treatment of seawater containing organic pollutants have been published, which are shown below.…”
Section: Elimination Of Organic Pollutants In Seawater By Ultrasoundmentioning
confidence: 99%
“…Since 2000 several papers have demonstrated that organochlorinated compounds, pharmaceuticals, plasticizers, industrial additives, among others, are present in seawater causing its pollution [20] , [76] , [77] , [78] . Also, we can mention that seawater has great potential as a processing medium for dyeing steps in the textile industry, resulting in seawater waste loaded with dyes [79] , [80] . Therefore, many proofs of concept about the sonochemical treatment of seawater containing organic pollutants have been published, which are shown below.…”
Section: Elimination Of Organic Pollutants In Seawater By Ultrasoundmentioning
confidence: 99%
“…They make up 70 % of all dyes and are used in industries like printing, food, pharmaceuticals, and cosmetics. [8][9][10] The conventional method for producing these compounds is through diazo-coupling, which involves combining a diazonium salt with the appropriate active methylene compound. [11] Azo-compounds have been shown to possess intriguing biological properties, including in vitro antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Azo‐compounds are brightly colored dyes, characterized by the presence of an ‐N=N‐ double bond between two aromatic or heterocyclic rings. They make up 70 % of all dyes and are used in industries like printing, food, pharmaceuticals, and cosmetics [8–10] . The conventional method for producing these compounds is through diazo‐coupling, which involves combining a diazonium salt with the appropriate active methylene compound [11] .…”
Section: Introductionmentioning
confidence: 99%
“…The most common one is dyeing. When diazonium salts undergo diazo-coupling reactions, diazo compounds are produced with great coloring features [2,3], and some of the important diazo dyes are shown in Figure 1a. Other than dyeing, some of the diazo compounds have antimicrobial, anticancer, antibacterial, antioxidant, antibiotic, antifungal and anti-HIV activity (Figure 1b) [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%